THE MEDIATING EFFECTS OF LEAN LEADERSHIP ON THE INFLUENCE OF LEAN MANAGEMENT AND GEMBA PRACTICES TOWARDS SUSTAINABILITY PERFORMANCE OF NATIONAL BANK OF OMAN - Ali Suleiman Ali Al Rusheidi; Kamisah Supian (International Journal of Accounting, Finance and Business, 2022)
The objectives of paper is to investigate the mediating effect of lean leadership onthe influence of lean management and Gemba practices towards sustainable performance inthe National Bank of Oman. A total of 129 managers and employees in the Oman National Bankhas been selected through simple random sampling technique. The Partial Least Squares -Structural Equations Method (PLS-SEM) technique was applied to measure the model by usingSmart PLS software. The finding reveals that lean leadership has an indirect-only mediationrole in the association between lean management practices towards sustainability performance.This result indicates that the implementation of lean management practices supported by thelean leadership attributes by the managers may ends up contributes significantly tosustainability performance of the Oman National Bank. Besides, the finding also support theContingency Theory whereby the impact of lean management practices on sustainabilityperformance is mediated by contextual variable, namely as lean leadership. Therefore, thisstudy recommends that the leaders at the National Bank of Oman should be able to modify theirfrequent command and control style towards lean leadership by enhancing employees’engagement and self-development while implementing quality improvement managementstrategies.